Estimation of bovine equalizing units in India: A regional perspective - SIROHI, SMITA; CHAND, PREM; SHARMA, DEEPAK; SAXENA, RAKA (The Indian Journal of Animal Sciences, 2019)
Study was conducted to formulate region specific standard animal units (SAUs) more comprehensively by considering labour utilization as well as size of animals. Both primary as well as secondary data were used in the study. Primary data were collected from 2,700 households from 18 districts of nine states. Conversion coefficients were formulated by aggregating coefficients of bodyweight and labour utilization and giving appropriate weights based on the experts’ opinion. We found that the dairy farmers devoted majority of their time on care and maintenance of milch animals in the herd. Heifers got almost equal or even more priority in care and maintenance than the adult male bovines. The intensity of labour utilization in crossbred cow as compared to local adult female was higher. The overall conversion coefficients were higher for crossbred cow. The estimated regional coefficients will be helpful in estimation of costs and returns in not only in dairying but also in other livestock production. Besides the overall SAU, the separate estimation of SAU based on bodyweight and labour utilization pattern will serve the purpose of both social as well as biological research studies, particularly for studies carrying capacity, housing management and overall farm planning.